2000
DOI: 10.1128/aac.44.6.1494-1498.2000
|View full text |Cite
|
Sign up to set email alerts
|

Activity of the Novel Immunomodulatory Compound Tucaresol against Experimental Visceral Leishmaniasis

Abstract: Tucaresol, a novel immunomodulator, was inactive against Leishmania donovani amastigotes in both peritoneal and bone marrow macrophages in vitro at concentrations between 100 and 1 M, with toxicity to macrophages and parasites at 300 M. However, against L. donovani in BALB/c mice at doses between 80 and 1.25 mg/kg of body weight administered once daily by the oral route during days 7 to 11 of infection, an optimal dose of 5 mg/kg produced a 43.8 to 62.4% suppression of liver amastigotes, with significantly red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…The latter phenomenon has been shown to occur frequently with clinical field isolates during their adaptation to in vitro culture and will affect the outcome of in vitro Sb resistance determinations (L. Maes, unpublished data). Overall, the results obtained in the present study are within the range of published IC 50 s for L. donovani strain L82 (10,14,30,35): IC 50 s of 4.8 to 34.5 g Sb V /ml were reported for sodium stibogluconate against intracellular amastigotes; miltefosine exhibited IC 50 s of 0.18 to 13.6 M on promastigotes and 2.8 to 5.8 M on intracellular amastigotes, while amphotericin B showed IC 50 s of 0.003 to 0.15 M and 0.026 to 0.076 g/ml against promastigotes and intracellular amastigotes, respectively.…”
Section: Discussionsupporting
confidence: 76%
“…The latter phenomenon has been shown to occur frequently with clinical field isolates during their adaptation to in vitro culture and will affect the outcome of in vitro Sb resistance determinations (L. Maes, unpublished data). Overall, the results obtained in the present study are within the range of published IC 50 s for L. donovani strain L82 (10,14,30,35): IC 50 s of 4.8 to 34.5 g Sb V /ml were reported for sodium stibogluconate against intracellular amastigotes; miltefosine exhibited IC 50 s of 0.18 to 13.6 M on promastigotes and 2.8 to 5.8 M on intracellular amastigotes, while amphotericin B showed IC 50 s of 0.003 to 0.15 M and 0.026 to 0.076 g/ml against promastigotes and intracellular amastigotes, respectively.…”
Section: Discussionsupporting
confidence: 76%
“…Some efforts have been devoted to searching for new antileishmanial drugs during the past 2 decades (2,6,15,21,22,25,30,33,38). One of the strategies for development of new antileishmanial drugs is to identify some unique enzymes, which exist only in the parasite and play important role in energy metabolism, as targets, and then to find or design inhibitors of these enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…This resistance occurred in 5 to 70% of patients in some areas of endemicity (28, 36). There is, therefore, a great and urgent need for the development of new, effective, and safe drugs for the treatment of leishmaniasis.A number of investigations to explore potential antileishmanial drugs have been carried out during the last 2 decades (2,6,15,21,22,25,30,33,38). We have previously reported that chalcones have potent antileishmanial and antimalarial activities and might be developed into a new class of antileishmanial drugs (7-10, 39).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the L. major model, prophylactic costimulation, including engaging the CD40 ligand and CD40 pathway by anti-CD40 injection, promotes Th1-cell responses and control over infection (61). The effect of the oral agent tucaresol in visceral infection also probably reflects T-cell costimulation (161).…”
Section: New Antileishmanial Agents or Application Of Existing Drugsmentioning
confidence: 99%